Community system of social support - Włoch, Krzysztof; Jaroszyński, Janusz; Warchoł-Sławińska, Ewa; Jurek, Anna; Drop, Bartłomiej; Furtak-Niczyporuk, Marzena (Polish Journal of Public Health, 2017)
Community System of Social Support is the basis of modern health care systems not only in Poland but all over the world in the prophylaxis-treatment-rehabilitation procedure. In Poland, family doctors, commune councils and territorial self-governments are involved in it. Family doctors perform a substantial function, whereas commune councils and territorial self-governments an administrative one. The principle of the system work is evaluation of its benefits. Its aim is the reduction of the number of patients who abuse alcohol and those who abuse alcohol despite treatment.